2013
DOI: 10.1155/2013/341862
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations, Treatment, and Outcome of Hospitalized Patients with Plasmodium vivax Malaria in Two Indian States: A Retrospective Study

Abstract: This was a retrospective study done on 110 patients hospitalized with P. vivax malaria in three medical college hospitals, one in the union territory of Chandigarh and the other two in Gujarat, that is, Ahmedabad and Surat. The clinical presentation, treatment, and outcome were recorded. As per WHO criteria for severity, 19 of 110 patients had severe disease—six patients had clinical jaundice with hepatic dysfunction, three patients had severe anemia, three had spontaneous bleeding, two had acute respiratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Overall, there was significant burden of anaemia among women in Jharkhand and particularly during pregnancy [ 23 ]. Our observations regarding anaemia are in accordance with the findings from other studies in Jharkhand [ 23 ], across India [ 41 , 42 ], and most relevant study by Nosten et al [ 43 ] in which they have demonstrated that women who had malaria at any time were more likely to be anaemic than women without malaria. Among multifactorial involvement in malarial anaemia are included haemolysis of parasitized erythrocytes and increased clearance of nonparasitized ones as well as an inadequate bone marrow response [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, there was significant burden of anaemia among women in Jharkhand and particularly during pregnancy [ 23 ]. Our observations regarding anaemia are in accordance with the findings from other studies in Jharkhand [ 23 ], across India [ 41 , 42 ], and most relevant study by Nosten et al [ 43 ] in which they have demonstrated that women who had malaria at any time were more likely to be anaemic than women without malaria. Among multifactorial involvement in malarial anaemia are included haemolysis of parasitized erythrocytes and increased clearance of nonparasitized ones as well as an inadequate bone marrow response [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were also reported by Gehlawat et al (36) and Singh et al (37). Malarial infections are reported to be related to occupation as some work and environmental conditions may prove to be conducive to the spread of malaria (38). The findings of the current study highlight the fact that most of the patients suffering from malaria were students, which pertains more to their age group than their occupation.…”
Section: Discussionsupporting
confidence: 90%
“…Malaria remains a major public health problem worldwide. Plasmodium falciparum is the parasite species causing the lethal form of the disease whilst Plasmodium vivax has long been considered a parasite causing mild disease, thereby diverting attention away from this species regarding research; however, recent studies have reported that this species also causes severe clinical syndromes [ 1 , 2 ]. Even though both species infect humans, they both emerged from different evolutionary lineages; whilst P. vivax shares a common ancestor with Asian non-human primate malaria, P. falciparum has diverged from parasites infecting great apes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%